2019
DOI: 10.1111/jcal.12384
|View full text |Cite
|
Sign up to set email alerts
|

Inquiry‐based learning and retrospective action: Problematizing student work in a computer‐supported learning environment

Abstract: We examined student performance in a computer-supported learning environment after students undertook, among others, a graphing task within an inquiry context.Students were assigned in two conditions: (a) Students were given one variable, and they had to select the second one to construct their graph; (b) students were given four variables, and they had to select two to construct their graph. Both conditions problematized student work by triggering retrospective action, where students returned to previous stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In addition, Xenofontos et al (2020) indicated that the core components of the inquiry cycle are carefully choreographed because the stages and steps have interrelated concepts. Hsiao et al (2017) also proposed an inquiry model design based on a circular inquiry model that could help students construct knowledge through repetitive steps.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Xenofontos et al (2020) indicated that the core components of the inquiry cycle are carefully choreographed because the stages and steps have interrelated concepts. Hsiao et al (2017) also proposed an inquiry model design based on a circular inquiry model that could help students construct knowledge through repetitive steps.…”
Section: Methodsmentioning
confidence: 99%
“…In IBL, students are presented a scientific question and by performing investigations or collecting data, they are going to find an answer to this question. Based on the results of the investigations, students infer what this means for the subject domain [3]. In contrast to traditional teaching where students often confirm knowledge, in IBL students construct meaning.…”
Section: A Inquiry Based Learningmentioning
confidence: 99%
“…In IBL, students are presented a scientific question and by performing investigations or collecting data, they are going to find an answer to this question. Based on the results of the investigations, students infer what this means for the subject domain (Vorholzer, von Aufschnaiter, & Boone, 2020;Xenofontos, Hovardas, Zacharia, & de Jong, 2020). In contrast to traditional teaching where students often confirm knowledge, in IBL students construct meaning.…”
Section: Inquiry Based Learningmentioning
confidence: 99%
“…For the participating teachers this study entailed two innovations at the same time, the introduction of a student-centered IBL pedagogy (Vorholzer et al, 2020;Xenofontos et al, 2020) in which the student groups determine the pace, the order of going through an ILS, and the way they want to collaborate in their group, as well as the use of a digital environment (Ton de Jong et al, 2014) in a complex school context.…”
Section: Teacher Participation and Commitmentmentioning
confidence: 99%